Immunohistochemical Study of the β-Chemokine Receptors CCR3 and CCR5 and Their Ligands in Normal and Alzheimer’s Disease Brains - Xia, MengQi (American Society for Investigative Pathology, 1998)
Chemokines belong to an expanding family of cytokines the primary function of which is recruitment of leukocytes to inflammatory sites. Recent evidence has shown their presence in the central nervous system. Because inflammatory responses have been implicated in the pathogenesis of Alzheimer’s disease (AD), we studied the expression of CCR3, CCR5, and their ligands in normal and AD brains by immunohistochemistry. CCR3 and CCR5 are present on microglia of both control and AD brains, with increased expression on some reactive microglia in AD. Immunohistochemistry for MIP-1β, MIP-1α, RANTES, eotaxin, and MCP-3 (ligands for CCR5 and/or CCR3) revealed the presence of MIP-1β predominantly in a subpopulation of reactive astrocytes, which were more widespread in AD than control brains, and MIP-1α predominantly in neurons and weakly in some microglia in both AD and controls. Many of the CCR3(+) or CCR5(+) reactive microglia and MIP-1β(+) reactive astrocytes were found associated with amyloid deposits. Immunoreactivity for eotaxin, RANTES, and MCP-3 were not detected. Detection of these β-chemokine receptors on microglia and some of their ligands in reactive astrocytes and neurons as well as microglia suggests a role for this system in glial-glial and glial-neuronal interactions, potentially influencing the progression of AD.